Exploring the potential of freshwater algal species for biofuel production - Singh, Vijetna; Ikram, Sana Fatima; Tripathi, Bhumi Nath (Frontiers in Energy Research, 2023)
The present study demonstrates the potential of freshwater algal species collected from the natural habitats of Central India for biofuel production. Algal samples were collected from different waterbodies and were microscopically examined in the laboratory. Based on morphological features using the taxonomic keys, a total of 51 algal species (18 Cyanophyta, 22 Chlorophyta, 7 Bacillariophyta, and 4 Charophyta) were identified. Among them, 18 algal species were successfully purified in the laboratory and tested for their ability to produce biomass and lipid, which are the essential criteria to be qualified as suitable feedstock for biofuel production. The data on specific growth rates suggest that Chlorella vulgaris, Scenedesmus bijugatus, and Nitzschia recta were the fastest-growing species, whereas all the members of Cyanophyta showed relatively slower growth. The biomass productivity was higher in Chlorella vulgaris, Scenedesmus bijugatus, and Anabaena sp. but the lipid production was highest in Chlorella vulgaris followed by Haematococcus sp., whereas, the members of Cyanophyta showed the lowest lipid production. Further, we assessed the ability of biomass and lipid production and biochemical parameters of four selected algal species, Chlorella vulgaris, Scendemsus bijugatus, Anabaena sp., and Nitzschia recta due to their faster growth, higher biomass and lipid production and abundance. Based on cluster analyses of the values of lipid and biomass production of these species against internal N:P ratio, three distinct clusters were noticed, cluster 1: near 50:1, cluster 2: between 30:35, and cluster 3 between 15:20 cellular N:P ratios. High lipid and biomass productivity were observed between the 30:35 N:P ratio. Despite the metabolic significance of N and P for algae, more research is warranted to conclude anything precisely.